2015
DOI: 10.1016/j.tmp.2015.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Building a conceptual framework for determining individual differences of accessibility to tourist attractions

Abstract: This paper introduces a conceptual framework for determining individual differences of accessibility to tourist attractions. The framework includes three components: factors affecting accessibility to tourist attractions; the individual characteristics of tourists, such as age, gender; and other explanatory variables that assist in explaining why accessibility to tourist attractions varies. This research indicates that measures of accessibility should include not only commonly used factors such as socio-demogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 77 publications
0
19
0
3
Order By: Relevance
“…Since hotel guests of different travel types have different needs and values for hotel location (AlKahtani et al 2015), we further split the sample by traveler type and applied the specification from model 3 to different samples based on traveler type in models 7 to 11, shown in Table 6. Among the five models, accessibility_attractions is estimated to be positive in all models but is insignificant in model 10 (family travelers) and model 11 (travelers with friends).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since hotel guests of different travel types have different needs and values for hotel location (AlKahtani et al 2015), we further split the sample by traveler type and applied the specification from model 3 to different samples based on traveler type in models 7 to 11, shown in Table 6. Among the five models, accessibility_attractions is estimated to be positive in all models but is insignificant in model 10 (family travelers) and model 11 (travelers with friends).…”
Section: Resultsmentioning
confidence: 99%
“…Extant hotel research has identified an extensive array of attributes, such as commonly found cleanliness, location, and a safe and secure environment, that have a significant influence on travelers’ hotel selection and satisfaction (Dolnicar and Otter 2003; Rhee and Yang 2015; Tanford, Raab, and Kim 2012). For instance, travelers may select a hotel in such a location as to optimize their trip duration and maximize their utilities under the space-time limitations (AlKahtani et al 2015). In addition, consumer behavior literature has indicated that travelers’ hotel selection and satisfaction are also affected by a number of traveler-related factors, such as trip purpose (business vs. pleasure), length of stay, travel party size and time, frequency of visits, social-cultural background of tourists (nationality, geographic origin, cultural difference), past experience, and demographics, to name a few (McKercher and Lew 2004; Chan and Wong 2006).…”
Section: Literature Reviewmentioning
confidence: 99%
“…(1) Calculation of accessibility The measurement of intra-city accessibility is based on the choice of road networks and travel modes (Lin et al, 2014;AlKahtani et al, 2015). This paper chooses the cumulative cost weighted distance method to calculate the accessibility of each residential area.…”
Section: Methodsmentioning
confidence: 99%
“…滑雪旅游是一项依托冰雪资源, 集休闲、 运动、 观光、 度假于一体的新兴专项旅游形式 [1,2] 。全球的 滑雪旅游正处于高速发展阶段, 滑雪旅游是滑雪产 业的基础 [3] , 为各国冰雪旅游产业的开拓提供了机 遇。目前, 全球整体年滑雪人次约达 4 亿, 近 100 个 国家建设超过 6000 个滑雪场所 [4] [5] 。 俄罗斯的滑雪旅游已较为成熟 [6] [7] 。汲取俄罗斯滑雪旅游产业的发展经 验, 对完善我国滑雪旅游产业基础设施建设, 科学 有序地规划中国滑雪旅游产业发展路线有重要的 指导意义。 从可达性角度分析旅游资源区位优势和交通 建设, 对滑雪产业的规划具有重要意义。可达性是 指从某一位置通过交通网络达到目的地的便利程 度, 是区域经济发展的重要影响因素 [8,9] http://www.resci.net 游空间结构的影响成为可达性研究热点 [8][9][10][11] 。国外 学者从不同角度探究了交通运输对旅游目的地发 展的影响。Prideaux [12] 通过分析交通与旅游目的地 之间的可接近性关系, Khadaroo 等 [13] 建立引力模型 概念, 发现道路基础设施完善的区域更吸引旅游点 聚集; 从游客视角出发, Kozak [14] 与 Alkahtani 等 [15] 学 者认为交通的便捷可达度影响旅行者的出行决策 与满意程度, 是提高景点吸引力的重要决定因素。 国内学者采用多种可达性指标对旅游资源空间结 构进行综合评价。靳诚等 [16] 运用最短路径选择方法 计算城市景点的空间可达性, 并针对不同圈层的景 点可达性进行优化; 潘竟虎等 [17] 用最近邻指数、 K 指 数、 成本加权距离算法等, 探究了国家湿地公园的 空间分布特征, 从整体和县域尺度进行了可达性测 度分析, 从而为国家均衡配置生态资源提供参考; 蒋海兵等 [18] 借助最短路径算法和网络分析模块量化 可达时间, 认为高铁加强了客源地与旅游景点之间 的联系; 杨蕊萌 [19] 分析了高铁通车前后的冰雪景点 的加权旅行时间与经济潜力的可达性时空变化, 提 议应加强东北三省各区域均衡发展。众学者采用 空间统计学方法及可达性指标评估旅游资源的空 间结构及区域效应, 提出空间布局优化建议, 不仅 能够使人们外出休闲更加便利, 还能够最大限度地 合理配置并利用旅游资源 [20][21][22] 。 近年来, 全球化进程加速使得滑雪旅游成为国 内外旅游市场研究的热点。国外学者对滑雪运动 及冰雪旅游研究开始较早。第一类研究通过探究 滑雪旅游资源内部的构成, 发现旅游者的年龄、 收 入, 旅游地的景观结构、 设施配置都能够体现其价 值 [23,24] , 外部气候环境也会给冰雪资源的经济效益 带来潜在影响 [25] ; 第二类研究是通过对市场与消费 者的实际调查, 对雪场的环境价值及未来市场趋势 进行评价 [26][27][28] 。国内学者对滑雪旅游的研究集中在 东北地区, 并结合发达国家冰雪旅游开发的成功经 验, 为中国的冰雪旅游建言献策。有学者认为中俄 两国的冰雪产业合作空间具有巨大的潜力与优势, 俄罗斯冰雪旅游度假村项目对中国具有启示意义 [29][30][31] ; 还有学者揭示了中国滑雪场 "小集聚、 大分散" 的空 间形态格局, 提出立足于 "冰雪-气候" 驱动机制, 推进冰雪运动 "南展西扩" 战略 [2], , 并致力于提升人 工造雪技术 [32]…”
Section: 引言unclassified